Odpowiedzi

Najlepsza Odpowiedź!
2010-01-16T19:32:06+01:00
Więc mamy:
(2x -3)² + (2x +3)²-(2x-3)(2x+3)

podnosimy do kwadratu oraz korzystamy z różnicy kwadratów po prawej:
(4x²-12x+9)+(4x²+12x+9)-(4x²-9) = 4x²-12x+9+4x²+12x+9-4x²+9 =
9+4x²+9+9 = 4x²+27

teraz dla x=-1:
4x²+27 = 4*(-1)²+27 = 4+27 = 31.
2010-01-16T19:34:30+01:00
(2x -3)² + (2x +3)²-(2x-3)(2x+3) = 4x²-12x + 9 + 4x² + 12x + 9 - 4x - 9 = 8x² + 9 - 4x
8 × ( -1 ) + 9 - 4 × ( - 1 ) = -8 + 9 + 4 = 5
2010-01-16T20:14:47+01:00
(2x -3)² + (2x +3)²-(2x-3)(2x+3)=(4x²-12x+9)+(4x²+12x+9)-(4x²-9) = 4x²-12x+9+4x²+12x+9-4x²+9 =9+4x²+9+9 = 4x²+27=4x²+27 = (-4)²+27=16+27=43